Fostering Students’ Writing Skill by the Integration of Mall Application - Retno Dwigustini; Novita Sari; Susilawati Susilawati; Baiatun Nisa (Journal of Languages and Language Teaching, 2021)
Writing has been one of the most significant skill to acquire by high school students. In fact, students still find it difficult due to weak mastery of writing components and limited practice as well as exposure and facility. On these ground, utilizing MALL in hybrid learning setting is assumed to enhance their writing skill. Employing qualitative approach with classroom action research design conducted in 3 cycles, 20 high school students were involved in this study. The data were obtained using observation, test and interview. The findings suggested that online writing application can help promoting students’ writing skill proven by the score increase from cycle 1 to 3 as well as their participation. The students either perceived the MALL application positively.